Rediscovering the adult play group. Issue 2 (3rd April 2018) - Scott, David
ABSTRACT: The study of recurring groups of adults involved in common leisure activity is scant. Adult play groups are important to participants, and studying them furthers our understanding of the community-building potential of leisure. In this paper, I seek to rediscover adult play group by outlining five themes. Borrowing from Huizinga, I begin by arguing that participation in leisure activities contributes to the emergence of play groups. I then argue that group members strive collectively to facilitate order by creating boundaries that set themselves apart from others. I then explain that play groups vary in the extent to which friendships are integral to their long-term functioning. Next, I describe how play groups influence participants' frequency of involvement in leisure activities. Finally, I argue that play groups provide participants an important context for resisting dominant ideologies and discourses.